Polyurethane-based aluminum oxide heat-conducting gasket and processing technology thereof

By components such as biological basal alcohol, isocyanate, aluminum, and composite fiber fillers are used in polyurethane hot pads, and vacuum dehydration and heating coilction solidification are used. The stable problem has achieved efficient thermal conductivity and insulation performance.

CN119371809APending Publication Date: 2025-01-28SUZHOU TECHNO NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543091.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing polyurethane-based thermal conductivity gaskets are prone to bubbles during the preparation process, and their hardness is not stable enough, which affects their thermal conductivity and insulation properties.

Method used

Bio -yield, isocyanate, aluminum, alumina, composite fiber fillers, catalysts, and additives, etc., and prepare polyurethane aluminum oxide heat conductive pads through vacuum dehydration and heating intermodation solidification processes.

Benefits of technology

It improves the thermal conductivity, insulation performance and surface hardness of the thermal pads, enhance the resistance of external force indentation or deformation, and improve stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113209220000071
    Figure BDA0005113209220000071
  • Figure BDA0005113209220000081
    Figure BDA0005113209220000081
Patent Text Reader

Abstract

The invention relates to a polyurethane-based aluminum oxide heat-conducting gasket and a processing technology thereof, and relates to the technical field of heat-conducting gaskets, and the polyurethane-based aluminum oxide heat-conducting gasket is prepared from the following raw materials in parts by mass: 7-21 parts of bio-based polyol, 5-12 parts of isocyanate, 70-90 parts of aluminum oxide, 6-10 parts of composite fiber filler, 0.01-0.05 part of a catalyst and 0.5-1 part of an auxiliary agent; the composite fiber filler comprises ceramic fibers and basalt fibers. The processing technology comprises the following steps: mixing and dispersing bio-based polyol, aluminum oxide, a composite fiber filler, a catalyst and an auxiliary agent into a reaction kettle, heating, carrying out vacuum stirring dehydration, and naturally cooling to obtain a mixture for later use; adding isocyanate into the mixture, and uniformly stirring to obtain a heat-conducting mixture; and calendering the heat-conducting mixture into a sheet, and heating, crosslinking and curing to obtain the polyurethane-based aluminum oxide heat-conducting gasket. The heat-conducting gasket has the effect of improving the heat-conducting property and the insulating property of the heat-conducting gasket, and the heat-conducting gasket has stable surface hardness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermally conductive gaskets, and in particular to a polyurethane-based aluminum oxide thermally conductive gasket and a processing technology thereof. Background Art

[0002] Thermal pads are a type of material used to fill the air gap between heat generating components and heat sinks or metal bases. They are flexible and elastic and can cover very uneven surfaces. Their function is to conduct heat from separate components or the entire PCB (printed circuit board) to the metal housing or diffusion plate, thereby improving the efficiency and service life of heat generating electronic components.

[0003] Thermal pads are usually made of polymer materials with good thermal conductivity and insulation properties. They can effectively reduce the temperature of heating components and prevent overheating damage, while also reducing electromagnetic interference and noise.

[0004] In conventional reactions, polyurethane is produced by reacting a hydroxyl compound with an isocyanate compound. During the reaction, isocyanate is extremely sensitive to water vapor and reacts with water to produce carbon dioxide. At the same time, hydroxyl compounds may have residual moisture during production, and alumina powder also contains trace amounts of moisture. These problems can easily cause bubbles to form on the surface of the product, and the hardness is not stable enough, so there is room for improvement. Summary of the invention

[0005] In order to improve the stability of the thermally conductive gasket, the present application provides a polyurethane-based aluminum oxide thermally conductive gasket and a processing technology thereof.

[0006] The polyurethane-based aluminum oxide thermal conductive pad and its processing technology provided in this application adopt the following technical solutions: In the first aspect, the present application provides a polyurethane-based alumina thermally conductive pad, which adopts the following technical solution: A polyurethane-based alumina thermally conductive pad, the raw materials for preparing the same include the following components in parts by mass: Bio-based polyol 7-21 parts Isocyanate 5-12 parts Alumina 70-90 parts Composite fiber filler 6-10 parts Catalyst 0.01-0.05 parts Additives 0.5-1 part; The composite fiber filler comprises ceramic fiber and basalt fiber.

[0007] Alumina has the characteristics of high thermal conductivity and small particle size. When filled in the polyurethane matrix, it can form a microscopic heat conduction path, so that heat can be efficiently transferred. Its small particle size allows it to fill the gaps in the molecular chain, thereby reducing thermal resistance; ceramic fiber uses its high axial thermal conductivity to construct a long-distance rapid heat conduction channel in the matrix, synergizing with alumina; basalt fiber can enhance structural stability and assist in uniform heat distribution, thereby improving thermal conductivity; the polyurethane matrix generated by bio-based polyols and isocyanates has good insulation and can block conductive pathways. Alumina, as an inorganic insulating material, has high resistivity and can increase insulation resistance, thereby improving the insulation performance of the thermal gasket; alumina has high hardness, ceramic fiber has strong rigidity and can withstand external force without deformation, and basalt fiber can enhance structural stability. The three work synergistically to enhance the material's ability to resist external force indentation or deformation, thereby improving the surface hardness and stability of the thermal gasket.

[0008] Preferably, the bio-based polyol is modified to obtain a modified bio-based polyol, and the raw materials for preparing the modified bio-based polyol include a bio-based polyol body and a fluorine-containing polyimide.

[0009] The polyimide molecular chain contains a large number of aromatic rings and imide bonds, and has excellent thermal stability and high thermal conductivity. After using polyimide to modify bio-based polyols, the thermal conductivity of the synthesized polyurethane can be improved, and it synergizes with alumina to form an efficient thermal conductive network, thereby improving the thermal conductivity of the thermal conductive gasket. Polyimide has good insulation properties, so that the modified thermal conductive gasket can effectively isolate current and prevent leakage while having excellent thermal conductivity. The introduction of polyimide enhances the intermolecular force of the polyurethane matrix, thereby improving the surface hardness of the thermal conductive gasket and improving the stability of the surface hardness of the gasket.

[0010] Preferably, the raw materials for preparing the fluorinated polyimide include hexafluorodianhydride, pyromellitic dianhydride and meta-phenylenediamine.

[0011] Hexafluorodianhydride introduces fluorine atoms, which have strong electronegativity and can increase the polarity of the molecule, thereby enhancing the interaction force between molecules and helping to improve the insulation properties of the material. As important reaction monomers, pyromellitic dianhydride and metaphenylenediamine work together with hexafluorodianhydride to form a regular polyimide molecular structure, thereby improving the thermal stability and mechanical strength of the thermal conductive gasket. The addition of fluorinated polyimide enhances the intermolecular force of the polyurethane matrix, making the molecular structure tighter and improving the surface hardness and stability of the thermal conductive gasket.

[0012] Preferably, the mass ratio of hexafluorodianhydride, pyromellitic dianhydride and m-phenylenediamine is (0.8-2):1:1.

[0013] The fluorinated polyimide prepared according to the above mass ratio has good reaction performance and can effectively improve the thermal conductivity, insulation performance and surface hardness of the thermal conductive gasket.

[0014] Preferably, the alumina is subjected to modification treatment to obtain modified alumina, and the raw materials for preparing the modified alumina include highly dispersed alumina and modified epoxy resin.

[0015] Modified epoxy resin can improve the dispersibility of alumina in the polyurethane matrix. Alumina powder originally has a high thermal conductivity. After uniform dispersion, it can form more effective heat conduction pathways, reduce scattering and obstruction in the heat conduction process, and improve heat transfer efficiency. Epoxy resin itself has good insulation properties, and synergizes with alumina to further enhance the overall insulation capacity. The dispersibility and compatibility of modified alumina are increased, and the bond with the polyurethane matrix is ​​tighter. Epoxy resin enhances the interfacial bonding strength between alumina and the matrix, and can better transfer stress when subjected to external force, thereby improving the surface hardness of the thermal conductive gasket.

[0016] Preferably, the highly dispersed alumina is obtained by modifying alumina using a titanate coupling agent.

[0017] Titanate coupling agent can improve the dispersion of aluminum oxide in polymers, reduce the surface energy of aluminum oxide, reduce agglomeration, and make it evenly distributed in the polyurethane matrix, forming more effective heat conduction channels, reducing thermal resistance, and improving thermal conductivity. The improvement of dispersion and compatibility can also promote the stability of the system, thereby improving insulation performance and surface hardness.

[0018] Preferably, the raw materials for preparing the modified epoxy resin include an epoxy resin matrix and grafted modified graphene.

[0019] Grafted modified graphene has good thermal conductivity and compatibility. It can be evenly dispersed in the epoxy resin matrix to construct a thermal conductive network. When combined with alumina, the high thermal conductivity channels of graphene and the thermal conductivity pathways of alumina work together to effectively improve the heat transfer efficiency. Graphene can also reinforce the defects between polymer molecular chains, limit the movement of molecular chains, and resist deformation under external forces, thereby increasing the surface hardness of the thermal conductive gasket.

[0020] Preferably, the raw materials for preparing the grafted modified graphene include graphene and dopamine hydrochloride.

[0021] Dopamine hydrochloride can form a polydopamine coating on the surface of graphene, which improves the interfacial compatibility between graphene and the epoxy resin matrix, makes the graphene more evenly dispersed in the matrix, and builds a more efficient thermal conductive network. At the same time, the conjugated structure of polydopamine helps heat transfer, and combined with the high thermal conductivity of graphene itself, it accelerates the conduction speed of heat in the thermal gasket, and cooperates with the thermal conductivity pathway of aluminum oxide to further enhance the overall thermal conductivity effect; the adhesion brought by the polydopamine coating enables the graphene to be closely connected to the matrix, enhancing the stability of the overall structure, thereby improving the surface hardness and insulation performance of the thermal gasket.

[0022] In a second aspect, the present application provides a processing technology for a polyurethane-based alumina thermally conductive pad, which adopts the following technical solution: A processing technology for polyurethane-based aluminum oxide thermal conductive pads, comprising the following steps: The bio-based polyol, alumina, composite fiber filler, catalyst and additive are mixed and dispersed in a reaction kettle, heated and vacuum stirred for dehydration, and naturally cooled to obtain a mixture for use; isocyanate is added to the mixture, and stirred evenly to obtain a thermally conductive mixture; the thermally conductive mixture is rolled into a sheet, and heated and cross-linked and cured to obtain a polyurethane-based alumina thermally conductive gasket.

[0023] The components that may contain water are dehydrated by heating and vacuuming, eliminating the need to add a dehydrating agent. The moisture-sensitive isocyanate is added later, which reduces the impact of moisture on the system, reduces bubbles on the surface of the product, and improves the surface hardness and stability of the product. The polyurethane-based alumina thermal pad prepared according to the above steps has good thermal conductivity, insulation performance and surface hardness, and can effectively reduce the temperature of the heating device.

[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. Alumina has the characteristics of high thermal conductivity and small particle size. When filled in the polyurethane matrix, it can form a microscopic heat conduction path, so that heat can be efficiently transferred. Its small particle size allows it to fill the gaps in the molecular chain, thereby reducing thermal resistance; ceramic fiber uses its high axial thermal conductivity to construct a long-distance rapid heat conduction channel in the matrix, and synergizes with alumina; basalt fiber can enhance structural stability and assist in uniform heat distribution, thereby improving thermal conductivity; the polyurethane matrix generated by bio-based polyols and isocyanates has good insulation and can block the conductive path. Alumina, as an inorganic insulating material, has high resistivity and can increase insulation resistance, thereby improving the insulation performance of the thermal gasket; alumina has high hardness, ceramic fiber has strong rigidity and can withstand external force without deformation, and basalt fiber can enhance structural stability. The three work synergistically to enhance the material's ability to resist external force indentation or deformation, thereby improving the surface hardness and stability of the thermal gasket.

[0025] 2. The polyimide molecular chain contains a large number of aromatic rings and imide bonds, and has excellent thermal stability and high thermal conductivity. After using polyimide to modify bio-based polyols, the thermal conductivity of the synthesized polyurethane can be improved, and it synergizes with alumina to form an efficient thermal conductive network, thereby improving the thermal conductivity of the thermal conductive gasket. Polyimide has good insulation properties, so that the modified thermal conductive gasket can effectively isolate current and prevent leakage while having excellent thermal conductivity. The introduction of polyimide enhances the intermolecular force of the polyurethane matrix, thereby improving the surface hardness of the thermal conductive gasket and the stability of the surface hardness of the gasket.

[0026] 3. Grafted modified graphene has good thermal conductivity and compatibility. It can be evenly dispersed in the epoxy resin matrix to construct a thermal conductive network. When combined with alumina, the high thermal conductivity channel of graphene and the thermal conductivity path of alumina work together to effectively improve the heat transfer efficiency; graphene can reinforce the defects between polymer molecular chains, enhance the strength of epoxy resin, limit the movement of molecular chains, and resist deformation under external forces, thereby improving the stability of the surface hardness of the thermal conductive gasket. DETAILED DESCRIPTION

[0027] The present application discloses a polyurethane-based aluminum oxide thermally conductive pad and a processing technology thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw material description: The bio-based polyol model is FHB-195, purchased from Zhangjiagang Feihang Technology Co., Ltd., ceramic fiber is purchased from Nantong Enpu Thermal Technology Co., Ltd., basalt fiber is purchased from Changzhou Yibao New Material Technology Co., Ltd., isocyanate model is Wanhua PM-200, catalyst is dibutyltin dilaurate (CAS No.: 77-58-7), additives are antioxidant 1010, hexafluorodianhydride (CAS No.: 1107-00-2), pyromellitic dianhydride (CAS No.: 89-32-7), m-phenylenediamine (CAS No.: 108-45-2), dimethylacetamide (CAS No.: 127-19-5), acetic anhydride (CAS No.: 108-24-7), pyridine (CAS No.: 110-86-1), titanate coupling agent model is TTS (CAS No.: 61417-49-0), graphene was purchased from Dandong Rijin Technology Co., Ltd., dopamine hydrochloride (CAS No.: 62-31-7), and the epoxy resin model is E-44.

[0028] Example 1 7g of bio-based polyol, 90g of alumina, 6g of composite fiber filler, 0.01g of catalyst and 0.5g of additive were mixed and dispersed in a reactor, the mass ratio of ceramic fiber to basalt fiber in the composite fiber was 1:1, the temperature was raised to 100°C and vacuum stirred for dehydration until the moisture content was less than 100ppm, the stirring speed was 200rpm, and a mixture was obtained after natural cooling for use; 5g of isocyanate was added to the mixture, and the mixture was stirred evenly at a speed of 200rpm to obtain a thermally conductive mixture; the thermally conductive mixture was rolled into a 2mm thick sheet, and the polyurethane-based alumina thermally conductive gasket was obtained after heating and cross-linking and curing.

[0029] Example 2 21g of bio-based polyol, 70g of alumina, 10g of composite fiber filler, 0.05g of catalyst and 1g of additive were mixed and dispersed in a reactor, the mass ratio of ceramic fiber to basalt fiber in the composite fiber was 1:1, the temperature was raised to 100°C and vacuum stirred for dehydration until the moisture content was less than 100ppm, the stirring speed was 200rpm, and the mixture was obtained after natural cooling for use; 12g of isocyanate was added to the mixture, and the mixture was stirred evenly at a speed of 200rpm to obtain a thermally conductive mixture; the thermally conductive mixture was rolled into a 2mm thick sheet, and the polyurethane-based alumina thermally conductive gasket was obtained after heating and cross-linking and curing.

[0030] Example 3 14g of bio-based polyol, 80g of alumina, 8g of composite fiber filler, 0.03g of catalyst and 0.75g of additive were mixed and dispersed in a reactor, the mass ratio of ceramic fiber to basalt fiber in the composite fiber was 1:1, the temperature was raised to 100°C and vacuum stirred for dehydration until the moisture content was less than 100ppm, the stirring speed was 200rpm, and the mixture was obtained after natural cooling for use; 8.5g of isocyanate was added to the mixture, and the mixture was stirred evenly at a speed of 200rpm to obtain a thermally conductive mixture; the thermally conductive mixture was rolled into a 2mm thick sheet, and the polyurethane-based alumina thermally conductive gasket was obtained after heating and cross-linking and curing.

[0031] Preparation Example 1 Preparation of modified bio-based polyols 3.57 g of m-phenylenediamine was dispersed in 100 mL of dimethylacetamide to obtain a diamine solution. In an ice-water bath, 2.86 g of hexafluorodianhydride and 3.57 g of pyromellitic dianhydride were added to the diamine solution, and the mixture was continuously stirred at a speed of 200 rpm. The addition was completed within 2 hours. After the addition was completed, the temperature was raised to 25° C. and the mixture was stirred and reacted at 200 rpm for 8 hours to obtain a polyamic acid solution. 2 g of acetic anhydride and 0.5 g of pyridine were added to the polyamic acid solution, and the mixture was stirred and reacted at 60° C. at 200 rpm for 8 hours. The solvent was removed by rotary evaporation to obtain a fluorinated polyimide.

[0032] 5 g of fluorinated polyimide and 30 g of bio-based polyol were mixed into 200 mL of dimethylacetamide, and the mixture was stirred at 80° C. and 200 rpm for 6 h. The solvent was removed by rotary evaporation to obtain a modified bio-based polyol.

[0033] Preparation Example 2 Preparation Example 2 is based on Preparation Example 1. The only difference between Preparation Example 2 and Preparation Example 1 is that in Preparation Example 2, the amount of hexafluorodianhydride used is 5 g, the amount of pyromellitic dianhydride used is 2.5 g, and the amount of m-phenylenediamine used is 2.5 g.

[0034] Preparation Example 3 Preparation Example 3 is based on Preparation Example 1. The only difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the amount of hexafluorodianhydride used is 4.12 g, the amount of pyromellitic dianhydride used is 2.94 g, and the amount of m-phenylenediamine used is 2.94 g.

[0035] Preparation Example 4 Preparation Example 4 is based on Preparation Example 1, and the only difference between Preparation Example 4 and Preparation Example 1 is that hexafluorodianhydride is not added in Preparation Example 4.

[0036] Preparation Example 5 Preparation Example 5 is based on Preparation Example 1. The only difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, pyromellitic dianhydride is not added.

[0037] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the bio-based polyol is replaced by the modified bio-based polyol prepared in Preparation Example 1.

[0038] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the bio-based polyol is replaced by the modified bio-based polyol prepared in Preparation Example 2.

[0039] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the bio-based polyol is replaced by the modified bio-based polyol prepared in Preparation Example 3.

[0040] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the bio-based polyol is replaced by the modified bio-based polyol prepared in Preparation Example 4.

[0041] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the bio-based polyol is replaced by the modified bio-based polyol prepared in Preparation Example 5.

[0042] Preparation Example 6 Preparation of Highly Dispersed Alumina The alumina was washed three times with anhydrous ethanol and dried at 100°C for 5 hours to obtain dried alumina. 200 g of the dried alumina and 5 g of a titanate coupling agent were dispersed in 500 mL of anhydrous ethanol, and the mixture was stirred at 60°C at 200 rpm for 4 hours to obtain a product. The product was washed three times with deionized water and dried at 100°C for 6 hours to obtain highly dispersed alumina.

[0043] Preparation Example 7 Preparation of modified alumina 2 g of graphene was dispersed in a mixed solution of 300 mL of 0.01 mol / L Tris buffer (pH 8.5) and 100 mL of anhydrous ethanol, 0.2 g of dopamine hydrochloride was added, and the reaction was stirred for 6 h. The graphene was washed by centrifugation with deionized water and anhydrous ethanol for 3 times respectively, and then dried at 60°C and ground to obtain dopamine-grafted graphene.

[0044] 1 g of dopamine-grafted graphene and 40 g of epoxy resin were mixed and dispersed, stirred at 80° C. at a speed of 300 rpm for 3 h, and subjected to ultrasound for 1 h to obtain a modified epoxy resin.

[0045] 30 g of the modified epoxy resin and 170 g of the highly dispersed alumina prepared in Preparation Example 6 were mixed, and the mixture was stirred at 80° C. and 500 rpm for 3 h to obtain modified alumina.

[0046] Preparation Example 8 Preparation Example 8 is based on Preparation Example 7, and the only difference between Preparation Example 8 and Preparation Example 7 is that dopamine-grafted graphene is replaced by graphene.

[0047] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, alumina is replaced by the highly dispersed alumina prepared in Preparation Example 6.

[0048] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, alumina is replaced by modified alumina prepared in Preparation Example 7.

[0049] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, alumina is replaced by modified alumina prepared in Preparation Example 8.

[0050] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the composite fiber filler is replaced by ceramic fiber.

[0051] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that no composite fiber filler is added in Comparative Example 2.

[0052] Performance testing (1) Select "ASTM D5470 for characterization of thermal conductivity of thin thermally conductive solid electrical insulating materials" as the standard, test the thermal conductivity of the sample, test each sample three times, take the average value after measurement, and record the results in Table 1.

[0053] (2) Select "ASTM D2240 Standard Test Method for Testing Rubber Hardness Using a Durometer" as the standard, prepare the test specimens, and use a Shore durometer to measure the surface hardness of the material (Shore OO). Each specimen is tested three times, and the average value is taken after measurement. The results are recorded in Table 1.

[0054] (3) GB / T1410-2006 Volume Surface Resistivity Test Method was selected as the standard to test the volume resistivity of the sample. Each sample was tested three times and the average value was taken after measurement. The results are recorded in Table 1.

[0055] Table 1 Test results of thermal conductivity, surface hardness and insulation performance of thermal conductive gaskets As shown in Table 1, the thermal conductivity of Examples 1-3 is greater than 2.38 W / m·K, the hardness is greater than 53, and the volume resistivity is greater than 2.6*10 13 Ω.cm, it can be seen that the thermally conductive gasket prepared in the present application has good thermal conductivity, insulation performance and high hardness.

[0056] As can be seen from Table 1, the only difference between Example 4-8 and Example 3 is that in Example 4-8, the bio-based polyol is replaced with a modified bio-based polyol, and compared with Example 3, the thermal conductivity, insulation performance and hardness of Example 4-8 are improved; the fluorinated polyimide prepared within the limited range in Example 4-6 has good reaction performance and modification effect, while the thermal conductivity, insulation performance and hardness of Examples 7 and 8 are reduced. This is because the molecular structure and reaction performance of the polyimide will be affected if fluorinated dianhydride or ordinary dianhydride is not added, which will further affect the modification effect and the regularity of the molecular structure, thereby reducing the thermal conductivity, insulation performance and hardness.

[0057] As can be seen from Table 1, the only difference between Examples 9-11 and Example 3 is that: in Examples 9-11, alumina is replaced with modified alumina, and compared with Example 3, the thermal conductivity, insulation performance and hardness of Examples 9-11 are improved; in Example 9, alumina is replaced with highly dispersed alumina, and the highly dispersed alumina has good dispersibility and improved compatibility with polyurethane, thereby improving the thermal conductivity, insulation performance and hardness of the thermally conductive gasket; in Example 10, alumina is replaced with modified alumina, and the epoxy resin is modified by grafting modified graphene, and the resin is wrapped on the surface of the highly dispersed alumina powder, which further improves its dispersibility, thereby improving thermal conductivity, insulation performance and hardness; in Example 11, the grafted modified graphene is replaced with graphene, and the dispersibility of the unmodified graphene decreases, so that the modification effect is slightly inferior to that of Example 10.

[0058] It can be seen from Table 1 that the only difference between Comparative Examples 1 and 2 and Example 3 is that in Comparative Example 1, the composite fiber filler is replaced with ceramic fiber, and in Comparative Example 2, no composite fiber filler is added. Compared with Example 3, the antioxidant performance of Comparative Examples 1 and 2 is reduced. This is because the composite fiber filler is reduced, and the rigid support and heat conduction path in the three-dimensional network structure constructed by the polyurethane resin in the thermal conductive gasket are reduced, thereby reducing the thermal conductivity and hardness.

[0059] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A polyurethane-based alumina thermally conductive pad, characterized in that: The raw materials for preparation include the following components in parts by weight: Bio-based polyol 7-21 parts Isocyanate 5-12 parts Alumina 70-90 parts Composite fiber filler 6-10 parts Catalyst 0.01-0.05 parts Additives 0.5-1 part; The composite fiber filler comprises ceramic fiber and basalt fiber.

2. The polyurethane-based alumina thermally conductive pad according to claim 1, characterized in that: The bio-based polyol is subjected to modification treatment to obtain modified bio-based polyol, and the raw materials for preparing the modified bio-based polyol include bio-based polyol body and fluorine-containing polyimide.

3. The polyurethane-based alumina thermally conductive pad according to claim 2, characterized in that: The raw materials for preparing the fluorine-containing polyimide include hexafluorodianhydride, pyromellitic dianhydride and metaphenylenediamine.

4. The polyurethane-based alumina thermally conductive pad according to claim 3, characterized in that: The mass ratio of the hexafluorodianhydride, pyromellitic dianhydride and metaphenylenediamine is (0.8-2):1:

1.

5. The polyurethane-based alumina thermally conductive pad according to claim 1, characterized in that: The aluminum oxide is subjected to modification treatment to obtain modified aluminum oxide, and the raw materials for preparing the modified aluminum oxide include highly dispersed aluminum oxide and modified epoxy resin.

6. The polyurethane-based alumina thermally conductive pad according to claim 5, characterized in that: The highly dispersed alumina is obtained by modifying alumina with a titanate coupling agent.

7. The polyurethane-based alumina thermally conductive pad according to claim 6, characterized in that: The raw materials for preparing the modified epoxy resin include an epoxy resin matrix and grafted modified graphene.

8. The polyurethane-based alumina thermally conductive pad according to claim 7, characterized in that: The raw materials for preparing the grafted modified graphene include graphene and dopamine hydrochloride.

9. A processing technology applied to the polyurethane-based aluminum oxide thermally conductive pad according to any one of claims 1 to 8, characterized in that: The steps include: The bio-based polyol, alumina, composite fiber filler, catalyst and additive are mixed and dispersed in a reaction kettle, heated and vacuum stirred for dehydration, and naturally cooled to obtain a mixture for use; isocyanate is added to the mixture, and stirred evenly to obtain a thermally conductive mixture; the thermally conductive mixture is rolled into a sheet, and heated and cross-linked and cured to obtain a polyurethane-based alumina thermally conductive gasket.